A Successful Replication of "Dust Pollution From the Sahara and African Infant Mortality" - Nikolai M. Cook (Institute for Replication (I4R), 2022)
This analysis is an independent replication of Heft-Neal et al. (2020). The original authors (HBBVB) provide evidence that particulate matter air pollution increases infant mortality in 30 African nations between 2000 and 2015. They provide three effect estimates. Using ordinary least squares, a 10 μg/m3 increase in PM2.5 exposure results in an estimated 8.6% increase in infant mortality. Using dust in the Bod'el'e depression as an instrumental variable, the same exposure increases infant mortality by 23.6%. Using rainfall in the Bod'el'e depression, the same exposure increases infant mortality by 24.3%. Using similar data and independently developed procedures I find corresponding estimates of 3.4%, 31.0%, and 29.7%.
Keywords: 330